2018
DOI: 10.1093/ajcp/aqy063
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of PD-L1 Expression Detection in Non–Small Cell Lung Cancer (NSCLC) Tissue Biopsy Specimens Between OncoTect iO Lung Assay and Immunohistochemistry (IHC)

Abstract: The nonsubjective OncoTect iO Lung Assay has been shown to be at least as accurate and sensitive as IHC for the detection of PD-L1 expression while providing additional information to guide treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In NSCLC tumors, fewer macrophages and DCs were present in the TME compared with adjacent normal lung tissues which was consistent with previous research ( 10 ), indicating chronic inflammation or disrupted tumor homeostasis in these NSCLC patients. MDSCs are divided into polymorphonuclear (PMN) and monocytic (M) MDSCs ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In NSCLC tumors, fewer macrophages and DCs were present in the TME compared with adjacent normal lung tissues which was consistent with previous research ( 10 ), indicating chronic inflammation or disrupted tumor homeostasis in these NSCLC patients. MDSCs are divided into polymorphonuclear (PMN) and monocytic (M) MDSCs ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…For flow cytometry as described before ( 10 ), single cells from tumor tissues and paired adjacent normal tissues were washed and stained with Fixable Viability Stain 780 (BD Biosciences) for cell viability measurements. Then, cells were washed with stain buffer (BD Biosciences) and blocked with human Fc block (BD Biosciences) to block Fc receptors.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the same methodology has been used to examined the PD-L1 expression on tumor cells and immune cells isolated from nonsmall lung cancer specimens [20,21]. They showed that the results of flow cytometric detection of PD-L1 were highly concordant with the results using IHC and proposed that the differential quantification of PD-L1 on tumor cells and immune cells may allow for better prediction of response to anti-PD-1/PD-L1 antibody therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Studies analyzing PD‐L1 testing on lung carcinoma cytology specimens originated mostly from the USA, followed by publications arising from Italy, Canada, United Kingdom, China, Germany, Japan, India, Turkey and other countries. The Dako clone 22C3 was the most common clone analyzed on cytology specimens, followed by the Ventana SP263 clone 17–67 . The data collected included the clone type used in each study.…”
Section: Resultsmentioning
confidence: 99%